2007
DOI: 10.1124/jpet.106.118224
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis in Microencapsulated Juvenile Rabbit Chondrocytes Induced by Ofloxacin: Role Played by β1-Integrin Receptor

Abstract: Quinolone(s) (QNs) is widely used in infection therapy due to its good antimicrobial characteristics. However, QNs-induced arthropathy of immature animals has led to restrictions on the therapeutic use of these antimicrobial agents. The exact mechanism(s) of QNs-induced chondrotoxicity remain unknown. In the present study, we investigated the possible mechanism of ofloxacin (one typical QNs)-induced injuries of chondrocytes. Juvenile rabbit joint chondrocytes cultured in alginate microspheres were incubated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 38 publications
0
13
1
Order By: Relevance
“…Recently, OFLX has been demonstrated to induce apoptosis in microencapsulated juvenile rabbit chondrocytes in vitro (Sheng et al, 2007). However, as shown in our results, OFLX has a potential to induce some genes related to cytokines, chemokines and/or proteases productions in chondrocytes but not genes showing activated apoptosis pathway.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Recently, OFLX has been demonstrated to induce apoptosis in microencapsulated juvenile rabbit chondrocytes in vitro (Sheng et al, 2007). However, as shown in our results, OFLX has a potential to induce some genes related to cytokines, chemokines and/or proteases productions in chondrocytes but not genes showing activated apoptosis pathway.…”
Section: Discussioncontrasting
confidence: 51%
“…Dusp1 protein has been known to inactivate c-Jun N-terminal kinase (JNK) and p38 mitogen-activated protein kinase (MAPK) pathways (Theodosiou and Ashworth, 2002). Recently, OFLX has been reported to inactivate ERK/MAPK signaling pathway in microencapsulated juvenile rabbit chondrocytes (Sheng et al, 2007). Although it is unclear whether increased Dusp1 results from activation of MAPK pathways or causes inactivation, the present (Table 4).…”
Section: Discussionmentioning
confidence: 93%
“…Slightly reduced expression of αv integrin on chondrocytes is exhibited in juvenile dogs receiving difloxacin in vivo 42 , and the expression of other integrins are also decreased in ofloxacintre ated mouse chondrocytes in vitro 4 3 -4 5 . W hen chondrocytes from juvenile rabbit joint cartilage are cultured with ofloxacin in alginate microspheres, β 1 -integrin expression is primarily reduced, and this causes subsequent changes in the extracellular signal-regulated kinase 1/2 / mitogen-activated protein kinase signaling pathway, resulting in caspase-8-dependent apoptosis of chondrocytes; supplementation with Mg 2+ blocks the changes in integrin and apoptosis 46 . Oxidation and mitochondrial change-In an ex vivo study using the chondrocytes of rabbits treated with ofloxacin or pefloxacin, an increase in cellular respiratory burst was observed in young animal cells, but not in adult animal cells, followed by decreased mitochondrial activity (suggestive of an injured membrane) and an increased mitochondrial mass (increased membrane area) 47 .…”
Section: Cavity Formationmentioning
confidence: 99%
“…In microencapsulated chondrocytes from juvenile rabbits, ofloxacin markedly causes apoptosis via the caspase-8-dependent mitochondrial pathway by affecting the levels of ␤ 1 integrins and extracellular signal-regulated kinase (ERK)/MAPK signalling pathway. Using specific caspase inhibitors it was demonstrated that ofloxacin increased the level of Bax, tBid and p53 in a concentration-and time-dependent manner [18,19].…”
Section: Possible Mechanism Responsible For Chondrotoxic and Tendotoxmentioning
confidence: 99%